2015
DOI: 10.1016/j.soscij.2014.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Situational predictors of violent intentions: Results from a factorial survey

Abstract: a b s t r a c tThough many sociological and criminological theories of violence provide a role for both situational and individual-level factors, research largely focuses on individual-level characteristics. The current research, drawing on the psychological and sociological aggression literatures, utilizes a factorial survey approach to identify important situational risk factors. Multi-level regression results indicate that provocation, aggressive cues, and the presence of an audience are all statistically s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…The fact that the same respondent rates several vignettes provides a potential source of intraindividual variation, which must be controlled for to adjust standard errors. Therefore, multilevel random coefficient models have been suggested as an appropriate estimation procedure (Jasso, ; Hox, Kreft, and Hermkens, ; Lyons, ; Willits, ). Within this framework, the vignettes are considered the level 1 units nested within respondents, who become the level 2 units of analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The fact that the same respondent rates several vignettes provides a potential source of intraindividual variation, which must be controlled for to adjust standard errors. Therefore, multilevel random coefficient models have been suggested as an appropriate estimation procedure (Jasso, ; Hox, Kreft, and Hermkens, ; Lyons, ; Willits, ). Within this framework, the vignettes are considered the level 1 units nested within respondents, who become the level 2 units of analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, deviant peers (differential associations) and low self-control have been found to predict criminal intentions (Skrzypiec, 2017). Willits (2015) found that anger, low self-control, prior violence and peer violence were all risk factors for violent intentions.…”
Section: The Risk-protective Factor Approachmentioning
confidence: 95%
“…Nevertheless, the majority of those who engage in criminal behaviors are likely to hold criminal attitudes. In recognition of this fact, while most of the research on risk factors has focused on behavioral outcomes, scholars have increasingly been interested in examining risk and protective factors for antecedent cognitive outcomes, including both criminal attitudes and intentions (e.g., Mazerolle & Piquero, 1997 ; Walters, 2017 ; Willits, 2015 , 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, there is also evidence that the environment also affects emotional responses. According to Zajonc’s (1965) drive theory of social facilitation, the presence of other individuals in the environment increases arousal, and research suggests that onlookers can exacerbate a given conflict (Collins, 2009; D. Willits, 2015).…”
Section: Predictors Of Emotionality In Police–citizen Interactionsmentioning
confidence: 99%